Student Learning Outcomes in Tanzania’s Primary Schools : Implications for Secondary School Readiness - Asim, Salman; Chugunov, Dmitry; Gera, Ravinder (World Bank, Washington, DC, 2019)
This policy note is an attempt to systematically analyze and document emerging trends in the evolution of students’ learning outcomes in Tanzania’s primary schools. The note is based on two rounds of the Service Delivery Indicators Survey in Tanzania, 2014 and 2016, and provides guidance to the Government on: (1) regional, district and school-level variations in gains in pupil achievement scores; (2) student, teacher and school level factors associated with learning outcomes; and (3) key observable factors associated with highest gains in test scores. The good news is that the Government’s concerted reform efforts are showing positive results in quality of schooling: test scores in English, Math, and Kiswahili for Standard four pupils have improved significantly over time. They have improved all across Tanzania, with largest gains registered in disadvantaged targeted districts (EQUIP-T3), followed by rural areas. Low-performing regions are catching up as the impacts of several large-scale investment programs are taking root. These improvements in test scores appear to be associated with improvements in teacher effort and subject knowledge. Rising pupil-teacher-ratios pose risks to continued learning improvements, particularly as the Government is preparing for rapid expansion in enrolments in the wake of the Fee-Free Basic Education Policy. Students tested for 2016 will be entering Form 1 secondary in 2018-19. For the improvements in learning at the primary level to have maximum impact, particularly in disadvantaged regions supported by EQUIP-T, they will require immediate attention to and investments in secondary schools to take these students through the full cycle of quality basic education promised by FFBEP. Female students, overage students, and non-native Kiswahili speakers continue to lag behind in learning, posing threats to the long-term equity of the system. Careful measurement of teacher practices at secondary level can provide ways to supportteaching behavior conducive to the well-being of these children.